A Study of Cell Phone Market in the Primorye Trritory (Russia) - MARTYSHENKO, Natalya Stepanovna; KMET, Elena Borisovna; KIM, Angelina Georgievna (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The cell phone market with its huge scale is quite seesaw in nature. The article presents the research findings on consumer preferences in the local cell phone market of the Primorye Territory. Assessment of preferences was carried out according to a survey conducted by the author in October 2015. The preference analysis was conducted in the context of the two consumer segments - ‘students’ and ‘other consumers’. The article presents the assessment of the consumers’ preferences on cell phone brands, evaluation of market structure in terms of cell phones prices as well as other assessments. Conducted research confirmed the hypothesis that the young consumers of mobile devices are most sensitive to emergence of new brand phones with enhanced capabilities.